2006
DOI: 10.1136/adc.2005.091637
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of inherited metabolic disorders in the West Midlands, UK

Abstract: These results are similar to those of the comparison studies, although the overall birth prevalence is higher in this study. This is probably due to the effects of ethnicity and consanguinity and increasing ascertainment. This study provides useful epidemiological information for those planning and providing services for patients with IMDs, including newborn screening, in the UK and similar populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
7
12

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(160 citation statements)
references
References 15 publications
6
135
7
12
Order By: Relevance
“…In another review of cases of IEM diagnosed in the West Midlands of the United Kingdom (where approximately 11 percent of the population is from black and ethnic minority groups) during 1999 to 2003 found that the incidence of organic acidemias was 12.6 per 100,000 [40].…”
Section: International Studiesmentioning
confidence: 99%
“…In another review of cases of IEM diagnosed in the West Midlands of the United Kingdom (where approximately 11 percent of the population is from black and ethnic minority groups) during 1999 to 2003 found that the incidence of organic acidemias was 12.6 per 100,000 [40].…”
Section: International Studiesmentioning
confidence: 99%
“…Both types occur equally often (Dodds 2001). Among the different groups of inborn errors of metabolism, MD is the most frequent with an incidence of approximately 1:5,000 (Sanderson et al 2006;Smeitink et al 2006;Schaefer et al 2004) but likely to be much higher due to under diagnosis (Edmond 2009). Currently, there is no effective pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the genetic metabolic disorders are related to pathways of amino acid metabolism, fatty acid oxidation metabolism, organic acid metabolism, glycogen storage, and lysosomal storage. Furthermore, there are other genetic conditions that are not IMDs, such as congenital hypothyroidism (CH), congenital adrenal hyperplasia (CAH), cystic fibrosis (CF), sickle cell disease (SCD), glucose-6-phosphate dehydrogenase deficiency (4,6,7 ), and severe combined immunodeficiency (SCID) (see Table 1 in the Data Supplement that accompanies the online version of this review at http://www.clinchem.org/content/vol62/ issue5). For the purposes of this review, all these conditions (IMDs and non-IMDs) will be referred to as IMDs.…”
Section: Genetic and Metabolic Disordersmentioning
confidence: 99%
“…The aim is to provide early diagnosis and to prevent or ameliorate the long-term consequences of the disease for infants who are suffering from a treatable metabolic/ genetic, endocrine, or hematologic condition (1,2 ). Fur-thermore, NBS programs have an expanded role in follow-up, diagnosis, and treatment (3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Purpose Of Nbsmentioning
confidence: 99%